2023
DOI: 10.1111/joa.13945
|View full text |Cite
|
Sign up to set email alerts
|

Muscle morphology and architecture of the medial gastrocnemius between typically developing children with different ancestral background

Fenna Walhain,
Marlies Declerck,
Ruby Chin A Fat
et al.

Abstract: Muscle ultrasonography is frequently used to improve the understanding of musculoskeletal impairments in children with spastic cerebral palsy (SCP). So far, most studies on muscle morphology and architecture have included typically developing children and children with SCP with similar ancestry, being mainly Caucasian. Less is known about differences in muscle morphology between children with different ancestral backgrounds. Therefore, the aim of this study was to compare muscle morphology and architecture of … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 43 publications
0
1
0
Order By: Relevance
“…Knowledge of growth rates in typically developing children may have implications for understanding disordered growth, for example, in children with neurological disorders such as cerebral palsy. Currently, it is largely unknown if growth rates differ between muscles, because most studies of muscle growth in childhood have investigated only one muscle (Bell et al, 2021;Benard et al, 2011;Binzoni et al, 2001;De Beukelaer et al, 2023;D'Souza et al, 2019;Herskind et al, 2016;Morse et al, 2008;Walhain et al, 2023;Weide et al, 2015Weide et al, , 2020 or a few muscles (Böl et al, 2017;Handsfield et al, 2022;Modlesky & Zhang, 2020;Mogi & Wakahara, 2022;O'Brien et al, 2010;Peeters et al, 2023;Siebert et al, 2017;Williams et al, 2022;Yanagisawa et al, 2014). O'Brien et al (2010) reported that the four components of the quadriceps muscles undergo similar relative increases in volume from childhood to adulthood.…”
Section: Introductionmentioning
confidence: 99%
“…Knowledge of growth rates in typically developing children may have implications for understanding disordered growth, for example, in children with neurological disorders such as cerebral palsy. Currently, it is largely unknown if growth rates differ between muscles, because most studies of muscle growth in childhood have investigated only one muscle (Bell et al, 2021;Benard et al, 2011;Binzoni et al, 2001;De Beukelaer et al, 2023;D'Souza et al, 2019;Herskind et al, 2016;Morse et al, 2008;Walhain et al, 2023;Weide et al, 2015Weide et al, , 2020 or a few muscles (Böl et al, 2017;Handsfield et al, 2022;Modlesky & Zhang, 2020;Mogi & Wakahara, 2022;O'Brien et al, 2010;Peeters et al, 2023;Siebert et al, 2017;Williams et al, 2022;Yanagisawa et al, 2014). O'Brien et al (2010) reported that the four components of the quadriceps muscles undergo similar relative increases in volume from childhood to adulthood.…”
Section: Introductionmentioning
confidence: 99%